SPATIAL AND ARCHITECTURAL DESIGN ASPECTS IN COMMUNITY BASED MOSQUES - Maslucha, Luluk (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2012)
Indonesia as one of the biggest Muslim countries in the world are very rich in the quality and quantity ofmosques architecture. The largest number of mosques in Indonesia is designed, built, and developed by localcommunities. Unfortunately, the potention of these kind of mosques is often unconsciously forgotten in thefield of architectural studies. Therefore, this research is held to define these mosques’ spatial andarchitectural design aspects which were considered as appropriate for the needs of their local communities’.As a descriptive-qualitative architectural research, the methods employed in this research are (1) fieldsurveying, (2) architectural documenting, and (3) informal interview, which were held in three purposivesample of mosques: Masjid An-Nur Jagalan, Masjid Gading Pesantren, and Masjid Jami’ Kauman Malang. Thesethree mosques were chosen because of their close relations with their surrounding communities and their longtime developments by their local societies. The result of this study shows that some specific spatial andarchitectural elements which were found in these community based mosques are (1) the scale, size, and depthof space, (2) the classification and the placement of space, (3) the architectural expressions, (4) the openness,the boundaries, and the relationship between spaces, (5) the athmospherical qualities of space, (6) theclassification of the users in spaces, (7) the intensity of the users in spaces, and (8) the manner and theposition of the users in spaces.